ANALISIS KEAMANAN WEBSITE UNIVERSITAS INTERNASIONAL BATAM MENGGUNAKAN METODE ISSAF - Stefanus Eko Prasetyo; Nurul Hassanah (Teknik Informatika, 2021)
With the support of various types of media for delivering information, technological developments change over time. To facilitate access to information, one of them can use the media website. With the development of website technology, more and more parties are using it as a supporting medium for information transmission, including educational institutions in Indonesia. However, many administrators do not understand the security of the website created but pay more attention to the appearance and function of the website. As a result, there were cases of hacker attacks on websites that resulted in data leaks and changes in website appearance. Therefore, it is important to realize the importance of website security to prevent leakage of important data. Because there have been cases of hacker attacks that have occurred several times, the researchers conducted a security analysis of the main website of the Universitas Internasional Batam Institute using the ISSAF method.